Kajian Efek Rokok Elektrik terhadap Kesehatan - Susana Elya Sudradjat (Jurnal Kedokteran Meditek, 2019)
The phenomenon of smoking has never stopped until now, with many pros and contras surrounding this phenomenon. In addition to conventional cigarettes, there are different types of smoking including shisha, cigars, and electric cigarettes. Many cigarette addicts are now switching to electric cigarettes, but the side effects are almost the same as conventional cigarettes. Studies found that there are various dangerous diseases that can be caused by smoking e-cigarettes including various organ damages and addiction. Therefore, e-cigarettes should be avoided.